2017
DOI: 10.1007/s00428-017-2212-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the budding and depth of invasion (BD) model in oral tongue cancer biopsies

Abstract: 1It is of great clinical importance to identify simple prognostic markers from preoperative 2 biopsies that could guide treatment planning. Here, we compared tumor budding (B), depth 3 of invasion (D) and the combined scores (i.e. BD histopathologic model) in preoperative 4 biopsies and the corresponding postoperative specimens of oral tongue squamous cell 5 carcinoma (OTSCC). Tumor budding and depth of invasion were evaluated in the pre-and 6 postoperative samples from 100 patients treated for OTSCC. Sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 37 publications
1
68
1
5
Order By: Relevance
“…revealed that depth of invasion was not associated with DFS; however, the combination prognostic model, tumour budding and depth of invasion (BD scoring from 0 to 2) was able to predict the behaviour of early‐stage OSCC patients. Recently, this histopathological model has validated an agreement between pre‐operative biopsies and postoperative samples, suggesting that analysis of the BD model from representative biopsies could be used for the treatment planning . Hori et al .…”
Section: Discussionmentioning
confidence: 82%
“…revealed that depth of invasion was not associated with DFS; however, the combination prognostic model, tumour budding and depth of invasion (BD scoring from 0 to 2) was able to predict the behaviour of early‐stage OSCC patients. Recently, this histopathological model has validated an agreement between pre‐operative biopsies and postoperative samples, suggesting that analysis of the BD model from representative biopsies could be used for the treatment planning . Hori et al .…”
Section: Discussionmentioning
confidence: 82%
“…The findings of these studies (Table ) indicated that tumour budding is an evaluable histopathological parameter in biopsy specimens and could be used as a reliable prognosticator for patient survival. The studies evaluated tumour budding in pretreatment samples in the following cancers: five studies (four cohorts) on rectal cancer, two on colorectal cancer and three (two cohorts) on oral cancer . There was one study on breast cancer, one on epidermoid anal cancer and one on cancer of the external auditory canal …”
Section: Resultsmentioning
confidence: 99%
“…In cancer of the external auditory canal, a single study showed that pretreatment tumour budding is associated with expression of laminin 5‐γ2 and predicts disease‐specific survival . Of note, a significant correlation between tumour budding in pre‐operative biopsies and postoperative samples was reported in colorectal cancer,, breast cancer and oral cancer …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also showed that TB was correlated with DOI in cT1‐2N0 OSCC and both of them are correlated with LNM and poor prognosis . Moreover, accumulating evidences indicated that TB is most promising as an independent prognostic factor for patient with cT1‐2N0 OSCC, even evaluated in biopsy specimens . These findings suggest that TB is a useful predictive factor for LNM and prognosis which can be evaluated in preoperative biopsies and guide treatment planning.…”
Section: Discussionmentioning
confidence: 99%